원전 담당 소방대들의 책임인식 비교 - 최해연(Hae-Youn Choi); 이상규(Sang-Kyu Lee); 김민희(Min-Hee Kim) (한국화재소방학회 논문지, 35(1), 2021)
책임인식은 의사결정, 역할조정, 직무수행에 영향을 미치며 효과적인 협력체계에서 중요한 요소이다. 본 연구에서는원전 관할소방대 186명과 원전 자체소방대 65명을 대상으로 책임인식 수준을 비교하고, 잠재계층분석을 통하여 각 소방대 내 책임인식의 양상이 어떠한지를 분석하였다. 연구 결과, 원전 화재에 대해 자체소방대의 역할과 책임이 관할소방대보다 더 우선시되었다. 무엇보다 두 조직 모두 집단 내 책임인식이 동질하지 않음이 확인되었다. 협력 상대와 비교 하여 원전 화재에 대한 상대적 책임을 묻는 질문들에 대해, 관할소방대에서는 ‘책임주도형’(11%)과 ‘책임분담형’(36%), 그리고 관할소방대의 책임을 낮게 인식하는 ‘책임위임형’(53%)이 나누어졌다. 자체소방대에서는 ‘책임주도형’(48%)과 ‘책임분담형’(52%)이 구분되었다. 조직구성원들이 동질적인 책임인식을 공유하지 않고 있다는 결과는 협력체계 내에 역할모호성이 존재함을 시사한다. 이에 조직 간 협력과 조정을 위한 인프라 개선이 필요함을 논의하였다. The responsibility mental model (RMM) is an important factor in an effective cooperation system that affectsdecision-making, role adjustment, and performance. For this purpose, 186 firefighters from an off-site fire brigade and 65firefighters from an on-site fire brigade participated in the study. We compared the levels of the RMM for a fire at anuclear plant and analyzed whether the RMM is shared internally in each fire brigade through latent profile analysis. Theresults showed that the responsibility of on-site fire brigades is prioritized for fire liability in nuclear plants. Both brigadesidentified the heterogeneity of the RMM. Firefighters from the off-site fire brigade were divided into three groups ofthinking they have ‘more responsibility’ (11%), ‘shared responsibility’ (36%), and ‘less responsibility’ (53%) than theircooperation partner. Firefighters from the on-site fire brigade were divided into two groups of ‘more responsibility’ (48%)and ‘shared responsibility’ (52%). The result that each fire brigade does not share a homogeneous RMM suggests theambiguity of roles in the cooperation system. The need for infrastructure for cross-organizational collaboration andcoordination is discussed. KCI Citation Count: 0